2024
DOI: 10.1037/trm0000243
|View full text |Cite
|
Sign up to set email alerts
|

The working life of a surf lifesaver: The traumatic experiences and consequences of New Zealand surf lifeguards.

Abstract: Surf lifeguards are exposed to a range of potentially traumatic events, yet little is known about the impact of this work. A cross-sectional online survey gathered information on personal and surf lifesaving trauma exposure, posttraumatic stress symptoms, posttraumatic growth, perceived social support, and perceived self-efficacy. Statistical analyses were performed to explore hypothesized relationships between these constructs and demographic variables. A total of 181 lifeguards, 17 years and older, were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
3

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 67 publications
(130 reference statements)
1
14
3
Order By: Relevance
“…Most Australian coastal safety research has focused on drowning prevention and wellbeing of Australians 7,8 and international tourists 9 . However, the mental wellbeing of SLS members is largely unexplored, with currently no scientific evidence from Australia and limited research internationally 10 . A recent New Zealand study reported surf lifeguards experienced an average of 16.78 traumatic events over their lifetime (both personal and SLS related) 10 .…”
Section: Competing Interestsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most Australian coastal safety research has focused on drowning prevention and wellbeing of Australians 7,8 and international tourists 9 . However, the mental wellbeing of SLS members is largely unexplored, with currently no scientific evidence from Australia and limited research internationally 10 . A recent New Zealand study reported surf lifeguards experienced an average of 16.78 traumatic events over their lifetime (both personal and SLS related) 10 .…”
Section: Competing Interestsmentioning
confidence: 99%
“…However, the mental wellbeing of SLS members is largely unexplored, with currently no scientific evidence from Australia and limited research internationally 10 . A recent New Zealand study reported surf lifeguards experienced an average of 16.78 traumatic events over their lifetime (both personal and SLS related) 10 . Male surf lifeguards were also found to have experienced more traumatic events than females 10 .…”
Section: Competing Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rooke and de Terte [ 4 ] presented the only study to examine exposure to PTEs, PTSS, and post-traumatic growth (PTG) in New Zealand SLS (N = 181). The findings revealed a relationship between PTEs experienced outside of SLS work and PTSS.…”
Section: Introductionmentioning
confidence: 99%
“…The findings revealed a relationship between PTEs experienced outside of SLS work and PTSS. Younger members (17–19 year olds) showed greater risk of PTSD than older lifeguards (27 + year olds), which also related to greater potential for PTG for younger lifeguards [ 4 ]. Interestingly, women showed a negative relationship associated with PTSS in comparison to men [ 4 ].…”
Section: Introductionmentioning
confidence: 99%